Analyzing barriers for stormwater management utilities - Marcelo Motta Veiga (IWA Publishing, 2021)
This study analyzed barriers for implementing stormwater utilities. Public budget constraints imply a need for prioritizing scarce public funds for financing water-related investment. In this sense, municipalities have ranked stormwater management services as a low priority compared to other public needs, causing them to be underfunded. The creation of stormwater utilities for securing resources should be supported through economic, technical, and legal arguments. There is a global water and sanitation access gap. Municipalities should dedicate themselves more to investigate how these gaps can be reduced, which will bring a higher benefit–cost ratio. Overruling these local governments and financing low priority interventions seems immoral. Furthermore, compulsory charges on public services that supply universal benefits are illegal. HIGHLIGHTS Stormwater management utilities.; Taxing water-related services.; Analyzing the sustainability of public services.; Cost and benefits of public services.; Infrastructure financing.;